STRATEGI PEMBELAJARAN YANG MENYENANGKAN UNTUK MENGOPTIMALKAN POTENSI SISWA - Mulyono, Mulyono (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
Happens in many countries, basic education is exceedingly oriented to formal academic education. Since children enter TK through SD, they are not given a chance to get an enjoyable learning and full of experience which is the basic of the real growth. The obserbing learning is lost. They learn is not for learning. The school should be formatted to be the most pleasure please for them because they can get many new things. Unfortunately, most of young students feel like in a class “Jail“. The trouble is a teacher feels like the most excellent people, most brilliant and understand with the children’s condition. Fortunately, nowadays there are many kinds of school that give any kinds alternatives of learning approach and give a lesson enjoyably and full of activities since TK or SD. The enjoyable education approach must be a main sufficient in realize the learning revolution for young student. Key words: approaching, education, enjoyable, young student